2020
DOI: 10.3390/ijerph17165873
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Korean Version of the Pregnancy Physical Activity Questionnaire

Abstract: The purpose of this study was to translate the Pregnancy Physical Activity Questionnaire, a semi-quantitative tool that asks participants about time spent on 32 activities, into Korean and verify its validity and reliability. In total, 363 pregnant women under prenatal care at an obstetrics and gynecology hospital and a postpartum care facility in Gyeonggi-do completed the Korean version of the Pregnancy Physical Activity Questionnaire. The questionnaire’s content validity, construct validity, concurrent valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…Scores for light- and moderate-intensity activity in our study were found to be higher than in the U.S., while the median for vigorous-intensity activity was in accordance with the findings of prior studies in the United States, Japan, Vietnam, China, Saudi Arabia, and South Korea [ 25 , 40 , 41 , 44 , 45 , 46 ]. Women’s modifying the intensity and type of their activities in pregnancy, especially through the later stages of pregnancy, might be reflected in their lower scores for vigorous activities and sports and recreational activities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Scores for light- and moderate-intensity activity in our study were found to be higher than in the U.S., while the median for vigorous-intensity activity was in accordance with the findings of prior studies in the United States, Japan, Vietnam, China, Saudi Arabia, and South Korea [ 25 , 40 , 41 , 44 , 45 , 46 ]. Women’s modifying the intensity and type of their activities in pregnancy, especially through the later stages of pregnancy, might be reflected in their lower scores for vigorous activities and sports and recreational activities.…”
Section: Discussionsupporting
confidence: 92%
“…The overall activity scores of our pregnant women were higher than overall scores observed in other studies [ 25 , 44 , 45 , 46 ]. In general, through criticism and advice, cultural norms and expectations often shape what pregnant women do with their bodies.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Cultural attitudes surrounding exercise during pregnancy may explain why low levels of vigorous PA were observed among our sample. 35 Recommendation against vigorous activity during pregnancy is prevalent in Asian populations, as it is viewed as potentially causing stress and harm to the mother and developing baby. 35 Lastly, since this study was done in a small sample of women recruited from a single hospital in Nepal, our ndings cannot be generalized with assurance to pregnant populations elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…We believe such information would be relevant in shaping maternal health interventions in the context of promotion of leisure-time physical activity, at least in this setting. Again, the prospective evaluation of physical activity using the PPAQ, a simple and short, reliable and valid tool, which has been used in several countries [47,[79][80][81][82][83][84], and the large sample of pregnant women serve as unique strengths of the study. To the best of the author's knowledge, previous studies examining physical activity during pregnancy in South Africa have not utilised such a large population as ours.…”
Section: Limitationsmentioning
confidence: 99%